Research on hybrid collaborative energy storage configuration in active distribution networks based on improved multi objective optimization - Xu, Mingcan; Lei, Guoping; Huang, Yinhua (Frontiers in Energy Research, 2025)
This article proposes a hybrid collaborative energy storage configuration method for active distribution networks based on improved particle swarm optimization to address the challenges of increased frequency regulation difficulty, increased voltage deviation, and reduced safety and stability when integrating wind and photovoltaic power generation into active distribution networks. The paper analyzes the factors that affect the energy storage configuration caused by the integration of renewable energy generation, analyzes the charging and discharging scheduling strategies of the energy storage system, and establishes corresponding mathematical models. The paper proposes an improved particle swarm optimization algorithm. Simulation and case analysis show that the algorithm can stably achieve optimized configuration, stable frequency regulation, and reduce carbon emissions of the energy storage system.